ANALISIS PERSONAL BRANDING FADIL JAIDI DI MEDIA SOSIAL (STUDI KASUS KONTEN INSTAGRAM, TIK TOK, DAN YOUTUBE) - Selly Septia Kurniati; Dini Valdiani; Ismail Taufik Rusfien (UNIVERSITAS PAKUAN, 2022)
Personal branding is something that is very important and needs to be owned by every individual. Personal branding is important for a Content Creator to be more easily recognized by the audience. This research was conducted in order to determine the personal branding of Content Creator Fadil Jaidi on social media Instagram, Tik Tok, and Youtube. This research also to know the differences and analyze the suitability of the personal branding criteria of Fadil Jaidi with the theory of Rampersad. This research uses a qualitative approach. Data collection techniques in this research were content analysis, in-depth interviews, and a literature study. In addition, checking the validity of the data using source triangulation. The results of this research indicate that the personal branding of Fadil Jaidi is joking and he has different personal branding criteria in each of his social media, but the most complex platform he uses is Instagram. Next, Fadil Jaidi in building personal branding in accordance with the authentic personal branding theory with the criteria, (1) Authenticity, (2) Integrity, (3) Consistency, (4) Specialization, (5) Authority, (6) Difference, (7) Relevance, (8) Visibility, (9) Persistence, (10) Kindness and (11) Performance.